PRO KONTRA GLOBALISASI PENDIDIKAN ISLAM - Aiman Fikri; I.M. Fatimah Zahro; Kasinyo Harto; Amilda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify the impact of globalization on Islamic education. The study aims to determine how globalization affects Islamic education, both positively and negatively so that it can develop appropriate strategies to face the challenges of globalization and strengthen Islamic education, such as building an appropriate Islamic education paradigm, implementing effective education, and improving teacher quality. The research method used is qualitative with a library approach or library study. Data collection techniques by understanding and studying theories from various literatures related to the literature such as books, journals and reviews that have been done. The results of this study indicate that globalization affects Islamic education and education in general. The pros or positive impacts observed from globalization on Islamic education include easy access to information, professional staff training according to international standards, more competitive education, creating a skilled and competitive workforce, creating innovation in education. Meanwhile, the cons or challenges to Islamic education include the rapid development of science and technology, demands for democracy in Islamic education, culture and moral summary, education costs.